Controllable preparation method of alpha-Fe2O3 nanostructure
By regulating the growth process of nanowires through amino acid molecules and guiding crystal growth in specific crystal planes using a hydrothermal method, α-Fe2O3 nanostructures with different morphologies were formed. This solved the bottleneck of the number of active sites in the self-assembly process of nanomaterials and improved catalytic performance.
Patent Information
- Application Number
- CN202510948589.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-11-04
AI Technical Summary
The existing self-assembly process of nanomaterials is limited by thermodynamic equilibrium, resulting in a bottleneck in the number of active catalytic sites, making it difficult to break through the thermodynamic limit and achieve high-efficiency catalytic performance.
By regulating the growth process of nanowires through amino acid molecules and using hydrothermal methods to guide crystal growth in specific crystal plane directions, α-Fe2O3 nanostructures with different morphologies, such as cubic, nanowires and elliptical particles, are formed, breaking the thermodynamic equilibrium and increasing the number of active sites.
Precise control of the morphology of α-Fe2O3 nanostructures was achieved, which improved catalytic performance, increased specific surface area and number of active centers, and broke through the thermodynamic limit.
Smart Images

Figure CN120887457A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of nanomaterial preparation, and particularly relates to a controllable preparation method of an alpha-Fe2O3 nanostructure. BACKGROUND
[0002] Iron oxide is always one of the core materials in the field of catalysis due to its advantages of rich reserves, low cost and environmental friendliness. Traditional iron oxide catalysts have shown basic catalytic activity in classic catalytic systems such as carbon monoxide oxidation and water-gas shift reaction. When the particle size is reduced to the nanometer level, the nanometer effect contained therein is promoting the qualitative leap of catalytic performance.
[0003] The current micro self-assembly process of nanomaterials is still limited by the thermodynamic equilibrium framework dominated by Gibbs free energy, resulting in an inherent thermodynamic threshold in the number of active catalytic sites in the material. This fundamental constraint makes it difficult to precisely control the multiple equilibrium states in the self-assembly process and break through the bottleneck of the number of active centers, which is the core difficulty and key breakthrough in the current improvement of nanocatalytic efficiency.
[0004] From the thermodynamic nature, nanomaterials tend to spontaneously reach the lowest energy stable configuration during self-assembly. This equilibrium driving mechanism often leads to the wrapping or passivation of active sites by inert structures. The core to break this dilemma is to establish a non-equilibrium state regulation strategy, which breaks the traditional thermodynamic equilibrium by introducing external field excitation, interface engineering modification or precise implantation of defects, and induces more high-energy coordination unsaturated sites on the material surface. The essence of this regulation is to reconstruct the dynamic path of self-assembly, like opening a new reaction channel in the energy landscape, so that more active centers are retained in the metastable state of the nanostructure.
[0005] The breakthrough of this scientific challenge not only needs to establish a quantitative model of active site formation from statistical thermodynamics, but also needs to combine in-situ characterization techniques to reveal the dynamic assembly mechanism under non-equilibrium state. When the precise control of the equilibrium-non-equilibrium state transformation in the process of nanoscale self-assembly is achieved, nanocatalytic materials will break through the thermodynamic limit and provide a new material design paradigm for constructing high-activity catalytic systems. SUMMARY
[0006] Therefore, some embodiments disclose a controllable preparation method of an alpha-Fe2O3 nanostructure, which comprises the following steps:
[0007] S1, amino acids are stirred and mixed with a NaOH aqueous solution to obtain a first mixed solution;
[0008] S2, a FeCl3·6H2O aqueous solution is mixed and stirred with the first mixed solution to obtain a second mixed solution;
[0009] S3, the urea aqueous solution, the polyethylene glycol-1500 aqueous solution and the second mixed solution are mixed and stirred to obtain a third mixed solution;
[0010] S4, the third mixed solution is subjected to a hydrothermal reaction, and the reaction product is separated to obtain an α-Fe2O3 nanostructure formed by amino acid molecule regulation of nanowire assembly.
[0011] Further, the controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: the concentration of the NaOH aqueous solution is 0.017M; the concentration of the FeCl3·6H2O aqueous solution is 0.2M; the concentration of the urea aqueous solution is 1M; the concentration of the PEG-1500 aqueous solution is 0.2g / mL; the amino acid in the first mixed solution is histidine; and the concentration of the histidine in the first mixed solution is 0.0133-0.067M, so that the obtained α-Fe2O3 nanostructure is a cubic-shaped nanoparticle.
[0012] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: the concentration of the NaOH aqueous solution is 0.017M; the concentration of the FeCl3·6H2O aqueous solution is 0.2M; the concentration of the urea aqueous solution is 1M; the concentration of the PEG-1500 aqueous solution is 0.2g / mL; the amino acid in the first mixed solution is histidine; and the concentration of the histidine in the first mixed solution is 0.1-0.166M, so that the obtained α-Fe2O3 nanostructure is a nanowire.
[0013] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: the concentration of the NaOH aqueous solution is 0.017M; the concentration of the FeCl3·6H2O aqueous solution is 0.2M; the concentration of the urea aqueous solution is 1M; the concentration of the PEG-1500 aqueous solution is 0.2g / mL; the amino acid in the first mixed solution is histidine; and the concentration of the histidine in the first mixed solution is 0.2-0.266M, so that the obtained α-Fe2O3 nanostructure is an elliptical-shaped nanoparticle.
[0014] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: in step S4, the temperature of the hydrothermal reaction is 140℃, and the reaction time is 12h.
[0015] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: in step S4, the reaction product is subjected to centrifugal separation, the centrifugal speed is 4000-6000rpm, and the centrifugal time is 8min.
[0016] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in some embodiments is as follows: in step S1, the first mixed solution is obtained by stirring and mixing for 10min.
[0017] Some embodiments disclose a controllable preparation method of the α-Fe2O3 nanostructure, in step S2, the second mixed solution is obtained by stirring and mixing for 30 min.
[0018] Some embodiments disclose a controllable preparation method of the α-Fe2O3 nanostructure, in step S3, the third mixed solution is obtained by stirring and mixing for 10 min.
[0019] Some embodiments disclose a controllable preparation method of the α-Fe2O3 nanostructure, in step S4, the hydrothermal reaction is carried out in a high-pressure reaction kettle containing a polytetrafluoroethylene liner.
[0020] The embodiment of the present application discloses a controllable preparation method of the α-Fe2O3 nanostructure, which utilizes amino acid molecules to regulate the growth process of nanowires, assembles the α-Fe2O3 nanostructure, and realizes the morphology regulation of the α-Fe2O3 nanostructure through the amino acid concentration, so that different shapes of nanostructures such as cubic, nanowire and elliptical particles are obtained. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 1 are shown in the figure.
[0022] Figure 2 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 2 are shown in the figure.
[0023] Figure 3 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 3 are shown in the figure.
[0024] Figure 4 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 4 are shown in the figure.
[0025] Figure 5 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 5 are shown in the figure.
[0026] Figure 6 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 6 are shown in the figure.
[0027] Figure 7 The SEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 7 are shown in the figure.
[0028] Figure 8 The TEM and XRD diagrams of the α-Fe2O3 nanostructure material obtained in Example 8 are shown in the figure. DETAILED DESCRIPTION
[0029] The term "example" as used herein to describe any implementations, is not to be construed as preferred or advantageous over other implementations. The performance test of the embodiments of the present application is carried out by using the conventional test method in the art, unless otherwise specified. It should be understood that the terms described in the embodiments of the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the disclosure of the embodiments of the present application.
[0030] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the embodiments of the present application belong; the test methods and technical means not specifically noted in the embodiments of the present application refer to the test methods and technical means commonly used by those skilled in the art.
[0031] The terms "substantially" and "approximately" as used herein are used to describe a small fluctuation. For example, they can mean less than or equal to ± 5%, such as less than or equal to ± 2%, such as less than or equal to ± 1%, such as less than or equal to ± 0.5%, such as less than or equal to ± 0.2%, such as less than or equal to ± 0.1%, such as less than or equal to ± 0.05%. Numerical data expressed or presented in the form of a range herein is used for convenience and brevity only, and should be construed as flexible to include not only the numerical values explicitly recited as the limits of the range, but also all individual numerical values or sub-ranges encompassed within the range. For example, a numerical range of "1-5%" should be interpreted to include not only the explicitly recited values of 1% and 5%, but also the individual values and sub-ranges within the indicated range. Thus, within this numerical range, there are individual values such as 2%, 3.5%, and 4%, and sub-ranges such as 1-3%, 2-4%, and 3-5%, etc. This same principle applies to ranges that only recite one numerical value. In addition, such interpretation applies regardless of the width of the range or the characteristics being described.
[0032] In this document, including in the claims, the conjunctions, such as "comprise", "include", "have", "with", "contain", "relate to", "accommodate", etc. are understood to be open-ended, i.e. to mean "including but not limited to". Only the conjunctions "consisting of" and "consisting exclusively of" are closed conjunctions.
[0033] In order to better illustrate the content of the present application, numerous specific details are given in the following specific embodiments. Those skilled in the art should understand that the present application can also be implemented without some specific details. In the embodiments, some methods, means, instruments, equipment, etc. which are well known to those skilled in the art are not described in detail, in order to highlight the main idea of the present application.
[0034] The technical features disclosed in the embodiments of the present application can be combined in any way without conflict, and the resulting technical solutions belong to the disclosure of the embodiments of the present application.
[0035] In some embodiments, the controllable preparation method of α-Fe2O3 nanostructures includes the steps of:
[0036] S1. Amino acids and NaOH aqueous solution are stirred and mixed to obtain the first mixed solution;
[0037] S2, FeCl3·6H2O aqueous solution is mixed and stirred with the first mixed solution to obtain the second mixed solution;
[0038] S3, urea aqueous solution, polyethylene glycol-1500 aqueous solution and the second mixed solution are mixed and stirred to obtain the third mixed solution;
[0039] S4 and the third mixed solution underwent a hydrothermal reaction, and the reaction products were separated to obtain α-Fe2O3 nanostructures assembled by nanowires regulated by amino acid molecules.
[0040] Typically, amino acid molecules are added to an aqueous NaOH solution to create an alkaline environment, followed by the addition of an aqueous FeCl3·6H2O solution to induce a precipitation reaction. Then, α-Fe2O3, assembled from nanowires, is formed via a hydrothermal process at a heating temperature of 140°C. During the hydrothermal reaction in the third mixed solution, the directional induction effect of the amino acid molecules guides the crystals to grow anisotropically along specific crystal planes, ultimately resulting in a characteristic elliptical morphology. α-Fe2O3 with this elliptical structure has a large specific surface area, enabling the generation of more active catalytic sites, thereby improving the catalytic performance of α-Fe2O3.
[0041] In hydrothermal reaction systems, when the solute supersaturation reaches a critical value, solute molecules or ions spontaneously aggregate to form crystal nuclei. For basic particles similar to nanowires, the formation mechanism may be as follows: first, initial crystal nuclei are formed in the solution through a homogeneous nucleation process; then, surrounding solutes continuously and directionally deposit on the surface of the crystal nuclei, gradually growing along a specific crystallographic direction, ultimately constructing a fibrous α-Fe2O3 nanostructure, i.e., a nanowire morphology.
[0042] Furthermore, by regulating the concentration of amino acid molecules, the functional groups and Fe can be precisely controlled. 3+ The strength of the complexation between the molecules is determined, thereby enabling precise control over the α-Fe2O3 nanostructure. This control mechanism essentially utilizes amino acid molecules as soft templates, forming a selective adsorption layer at the crystal growth interface through coordination, much like setting up "molecular guides" for crystal growth. This transforms the differences in complexation strength at different concentrations into the diversity of nanostructure morphology, from one-dimensional nanowires to spindle-shaped polyhedra, and then to hierarchical porous structures, achieving precise tailoring of the material's microstructure.
[0043] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, the concentration of NaOH aqueous solution is 0.017M; the concentration of FeCl3·6H2O aqueous solution is 0.2M; the concentration of urea aqueous solution is 1M; the concentration of PEG-1500 aqueous solution is 0.2g / mL, the amino acid in the first mixed solution is histidine, and the concentration of histidine in the first mixed solution is 0.0133-0.067M, and the obtained α-Fe2O3 nanostructure is a cubic-shaped nanoparticle.
[0044] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, the concentration of NaOH aqueous solution is 0.017M; the concentration of FeCl3·6H2O aqueous solution is 0.2M; the concentration of urea aqueous solution is 1M; the concentration of PEG-1500 aqueous solution is 0.2g / mL, the amino acid in the first mixed solution is histidine, and the concentration of histidine in the first mixed solution is 0.1-0.166M, and the obtained α-Fe2O3 nanostructure is a nanowire.
[0045] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, the concentration of NaOH aqueous solution is 0.017M; the concentration of FeCl3·6H2O aqueous solution is 0.2M; the concentration of urea aqueous solution is 1M; the concentration of PEG-1500 aqueous solution is 0.2g / mL, the amino acid in the first mixed solution is histidine, and the concentration of histidine in the first mixed solution is 0.2-0.266M, and the obtained α-Fe2O3 nanostructure is an elliptical nanoparticle.
[0046] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, in step S4, the hydrothermal reaction is carried out in a high-pressure reaction kettle containing a polytetrafluoroethylene liner, the hydrothermal reaction temperature is 140℃, and the reaction time is 12h; the reaction product is subjected to centrifugal separation, the centrifugal rotation speed is 4000-6000rpm, and the centrifugal time is 8min.
[0047] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, in step S1, the first mixed solution is obtained by stirring and mixing for 10min.
[0048] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, in step S2, the second mixed solution is obtained by stirring and mixing for 30min.
[0049] Some embodiments disclose a controllable preparation method of α-Fe2O3 nanostructure, in step S3, the third mixed solution is obtained by stirring and mixing for 10min.
[0050] The technical details are further exemplarily described below in combination with embodiments.
[0051] Example 1
[0052] In Example 1, the preparation method of the α-Fe2O3 nanostructure comprises the following steps:
[0053] S1, first prepare a NaOH aqueous solution with a concentration of 0.017 M, and then directly add 0.1 mmol of histidine (L-His) into 7.5 mL of the NaOH aqueous solution and stir for 10 min to obtain a uniform first mixed solution;
[0054] S2, then add 5 mL of a FeCl3·6H2O aqueous solution with a concentration of 0.2 M into the first mixed solution and continue to stir for 30 min to obtain a second mixed solution;
[0055] S3, sequentially add 0.25 mL of a urea aqueous solution with a concentration of 1 M and 0.5 mL of a PEG-1500 aqueous solution with a concentration of 0.2 g / mL into the second mixed solution and stir for 10 min to obtain a third mixed solution.
[0056] S2, place the third mixed solution into a polytetrafluoroethylene-lined high-pressure reaction kettle with a volume of 20 mL to perform a hydrothermal reaction, the reaction temperature is 140°C, and the reaction time is 12 h; centrifuge the obtained product at a speed of 4500 rpm for 8 min to obtain a precipitate.
[0057] In Example 1, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD diagrams are shown in FIGS. (a) and (b) of Figure 1 .
[0058] Example 2
[0059] In Example 2, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; and the amount of histidine is 0.25 mmol.
[0060] In Example 2, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD diagrams are shown in FIGS. (a) and (b) of Figure 2 .
[0061] Example 3
[0062] In Example 3, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; and the amount of histidine is 0.5 mmol.
[0063] In Example 3, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD diagrams are shown in FIGS. (a) and (b) of Figure 3 .
[0064] The SEM images of the α-Fe2O3 obtained from Examples 1, 2, and 3 show that the particles of the samples are basically in the shape of approximate cubes, the overall structure is relatively regular, and the surface looks relatively smooth without obvious protrusions or recessed structures. The size of the material is large, and the distribution in the image is uniform without obvious agglomeration or accumulation, indicating that the dispersibility is good.
[0065] Example 4
[0066] In Example 4, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; wherein the amount of histidine is 0.75 mmol.
[0067] In Example 4, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD images are shown in FIGS. (a) and (b) of Figure 4
[0068] Example 5
[0069] In Example 5, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; wherein the amount of histidine is 1 mmol, and the centrifugal speed is 6000 rpm.
[0070] In Example 5, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD images are shown in FIGS. (a) and (b) of Figure 5
[0071] Example 6
[0072] In Example 6, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; wherein the amount of histidine is 1.25 mmol, and the centrifugal speed is 6000 rpm.
[0073] In Example 6, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD images are shown in FIGS. (a) and (b) of Figure 6
[0074] The SEM images of the α-Fe2O3 obtained from Examples 4, 5, and 6 show that the sample product is composed of numerous small needle-like or fibrous structures, the structure is relatively fine and dense, and may have a large specific surface area. It is also found that there are multiple similar elliptical particles in the sample, which are assembled by many small fibrous structures.
[0075] Example 7
[0076] In Example 7, the preparation method of the α-Fe2O3 nanostructure refers to Example 1; wherein the amount of histidine is 1.5 mmol, and the centrifugal speed is 6000 rpm.
[0077] In Example 7, the precipitate is an α-Fe2O3 nanostructure, and the SEM and XRD graphs are shown in Figure 7 Fig. (a) and (b) in the middle.
[0078] Example 8
[0079] In Example 8, the preparation method of the α-Fe2O3 nanostructure is the same as that in Example 1; wherein, the amount of histidine is 2 mmol, and the centrifugal speed is 6000 rpm.
[0080] In Example 8, the precipitate is an α-Fe2O3 nanostructure, and the TEM and XRD graphs are shown in Figure 8 Fig. (a) and (b) in the middle.
[0081] From the SEM and TEM graphs of the α-Fe2O3 obtained in Examples 7 and 8, it can be seen that the samples are almost all assembled into similar elliptical particles, the particle surface presents rough texture, the arrangement is relatively compact, and the size is relatively uniform.
[0082] The controllable preparation method of the α-Fe2O3 nanostructure disclosed in the embodiments of the present application utilizes amino acid molecules to regulate the growth process of nanowires, assembles the nanowires into α-Fe2O3 nanostructures, and can realize the regulation of the generation of the α-Fe2O3 nanostructure through the amino acid concentration, so as to obtain nanostructures with different shapes such as cubic, nanowire and elliptical particle.
[0083] The technical solutions disclosed in the embodiments of the present application and the technical details disclosed in the embodiments are only exemplary to illustrate the inventive concept of the present application, and do not constitute a limitation on the technical solutions of the embodiments of the present application. Any conventional change, replacement or combination of the technical details disclosed in the embodiments of the present application has the same inventive concept as the present application, and is within the protection scope of the claims of the present application.
Claims
1. A controllable preparation method for α-Fe₂O₃ nanostructures, characterized in that, Including the following steps: S1. Amino acids and NaOH aqueous solution are stirred and mixed to obtain the first mixed solution; S2, FeCl3·6H2O aqueous solution is mixed and stirred with the first mixed solution to obtain the second mixed solution; S3, urea aqueous solution, polyethylene glycol-1500 aqueous solution and the second mixed solution are mixed and stirred to obtain the third mixed solution; S4 and the third mixed solution underwent a hydrothermal reaction, and the reaction products were separated to obtain α-Fe2O3 nanostructures assembled by nanowires regulated by amino acid molecules.
2. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, The concentration of NaOH aqueous solution was 0.017M; the concentration of FeCl3·6H2O aqueous solution was 0.2M; the concentration of urea aqueous solution was 1M; the concentration of PEG-1500 aqueous solution was 0.2g / mL. The amino acid in the first mixed solution was histidine. When the concentration of histidine in the first mixed solution was 0.0133~0.067M, the obtained α-Fe2O3 nanostructures were cubic nanoparticles.
3. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, The concentration of NaOH aqueous solution was 0.017M; the concentration of FeCl3·6H2O aqueous solution was 0.2M; the concentration of urea aqueous solution was 1M; the concentration of PEG-1500 aqueous solution was 0.2g / mL; the amino acid in the first mixed solution was histidine; when the concentration of histidine in the first mixed solution was 0.1~0.166M, the obtained α-Fe2O3 nanostructures were nanowires.
4. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, The concentration of NaOH aqueous solution was 0.017M; the concentration of FeCl3·6H2O aqueous solution was 0.2M; the concentration of urea aqueous solution was 1M; the concentration of PEG-1500 aqueous solution was 0.2g / mL; the amino acid in the first mixed solution was histidine; when the concentration of histidine in the first mixed solution was 0.2~0.266M, the obtained α-Fe2O3 nanostructures were elliptical nanoparticles.
5. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S4, the hydrothermal reaction temperature is 140℃ and the reaction time is 12h.
6. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S4, the reaction product is centrifuged at a speed of 4000-6000 rpm for 8 min.
7. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S1, the mixture is stirred for 10 minutes to obtain the first mixed solution.
8. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S2, the mixture is stirred for 30 minutes to obtain a second mixed solution.
9. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S3, the mixture is stirred for 10 minutes to obtain the third mixed solution.
10. The controllable preparation method of α-Fe₂O₃ nanostructures according to claim 1, characterized in that, In step S4, the hydrothermal reaction is carried out in a high-pressure reactor lined with polytetrafluoroethylene.